The Arab World Initiative and Regional Integration - Akhtar, Shamshad (World Bank, Washington, DC, 2012)
The March 24, 2010 ministerial consultation to discuss regional cooperation and integration initiatives for the Arab world was a key milestone in the Arab world initiative, one of the six strategic directions outlined by President Zoellick in October 2007. This important first round of regional deliberations was hosted under the patronage of the ministry of investment of Egypt. The backing of Egypt and its leadership in supporting cooperation within the region is critical given its strategic standing, location and resource base. Going forward, the plan is to rotate events to discuss Arab world cooperation through different locations across the region.